Prologue to the Coup of February 1921, Reza Shah’s Dictatorship - Khandagh, Najleh (Advances in Social Sciences Research Journal, 2014)
The period in which political activity in Iran flourished in comparatively free conditions and with considerable vigor was a remarkably brief one when viewed from the perspective of the long history that belongs to Iran. Most historians of Iran regard the emergence of the first political parties as coming with the Constitutional Revolution in 1905-11, and this preliminary stage of political activity lasted until 1921, after Reza Shah coming to power and ruling the country absolutism for twenty years in when the political parties and the trade unions went underground. Reza shah’s tyrannical rule and his inclination to Germany in the Second World War , ignored the Anglo-Russian ultimatum. The great powers, mainly Britain and Russia, forced him to resign in favor of his son (Mohammad Reza Shah) in 1941.I shall discuss, the pre period of Reza Shah which gave him opportunity to access to the throne and, I tried to show his dictatorial rule and emphasize on his tyrannical rule.